The Effectiveness of Electric Toothbrushes and Conventional Toothbrushes in Reducing Plaque Scores on School-Aged Children with Mental Impairment: Pilot Study - Rusmiati; Rosmawati; Sri Febrianti; Andriani (OPI Napoli, 2022)
Introduction: Improving the quality of life of children is one of the goals of the health development program. The growth of children's health is not discriminated against in this scenario. All children with special needs or impairments are covered by child health services, whether at Special Schools (SS), other institutions, or in the community. This study aimed to evaluated the effectiveness of using an electric toothbrushes, compared to conventional toothbrushes, in the reduction of dental plaque score. Methods: This study was designed as a quasi-experimental study with a pretest-posttest design. All school-aged children with mental impairment in SS Jambi City, Indonesia were included in this study. Overall, 20 children were assigned to the intervention group (n=10) and to the control group (n=10). The Personal Hygiene Performance-Modified (PHP-M) was used to examine plaque index for the assessment of dental and oral hygiene. Results: In the pretest-posttest, mean difference values in plaque scores were statistically significant in both the intervention (19.50±3.89, p<0.009) and control (17.90±1.61, p<0.001) groups. A statistically significant reductions was showed in mean post-test plaque index (p<0.001) in the intervention group compared to the control group (14.50 ±7.83; 32.80± 13.14, respectively). Conclusion: When compared to conventional toothbrushes, electric toothbrushes are more effective in reducing plaque scores in mentally retarded children at SS Jambi City.